Computer support for recording and interpreting family histories of breast and ovarian cancer in primary care (RAGs): qualitative evaluation with simulated patients. - Emery, J; Walton, R; Coulson, A; Glasspool, D; Ziebland, S; Fox, J (1999)
OBJECTIVES: To explore general practitioners' attitudes towards and use of a computer program for assessing genetic risk of cancer in primary care. DESIGN: Qualitative analysis of semistructured interviews and video recordings of simulated consultations. PARTICIPANTS: Purposive sample of 15 general practitioners covering a range of computer literacy, interest in genetics, age, and sex. INTERVENTIONS: Each doctor used the program in two consultations in which an actor played a woman concerned about her family history of cancer. Consultations were videotaped and followed by interviews with the video as a prompt to questioning. MAIN OUTCOME MESURESs: Use of computer program in the Consultation. RESULTS: The program was viewed as an appropriate application of information technology because of the complexity of cancer genetics and a sense of "guideline chaos" in primary care. Doctors found the program easy to use, but it often affected their control of the consultation. They needed to balance their desire to share the computer screen with the patient, driven by their concerns about the effect of the computer on doctor-patient communication, against the risk of premature disclosure of bad news. CONCLUSIONS: This computer program could provide the necessary support to assist assessment of genetic risk of cancer in primary care. The potential impact of computer software on the consultation should not be underestimated. This study highlights the need for careful evaluation when developing medical information systems.